PENGARUH PEMBELAJARAN TATAP MUKA TERBATAS MENGGUNAKAN MODEL KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR (JS (JURNAL SEKOLAH), 2023)
Abstract: This study aims to determine the effect of limited face-to-face learning using a cooperative jigsaw model on learning outcomes in Catholic Religious Colleges. This study used a quantitative approach with a one-group pretest and posttest design. The sample in this study was students totaling 30 people. Data collection techniques used are test measurements. Based on data analysis using the normality test and the Wilcoxon test, it is known that the significance value is 0.000